Synthetic Literature review of Organizational Forgetting - Turi, Jamshid Ali; Fatimah, Mahmud; Toheed, Hira; Sorooshian, Shahryar (Society for Science and Education, United Kingdom, 2019)
This paper covers comprehensive literature analysis on organizational forgetting. Work on organizational forgetting was synthesised in systematic and chronological order. Forgetting theories in organizational context have been widely discussed to comprehend forgetting in organizational context. Cognitive, social and behavioural factors of forgetting have been also cited in organization contextual application. All the theories, prevailing context and factors indicate, as evident from content analysis, have greater impact on organizational learning.